2003
DOI: 10.2965/jwet.2003.19
|View full text |Cite
|
Sign up to set email alerts
|

Photoreactivation of Enterohemorrhagic E. Coli, Vre and P. Aeruginosa Following Uv Disinfection

Abstract: UV disinfection is noted to have some problems, one of which is photoreactivation. Photoreactivation allows inactivated microorganisms to regain viability following UV disinfection. The objective of this study is to determine the susceptibility of enterohemorrhagic Escherichia coli (EHEC) O26, vancomycin resistant Enterococcus (VRE), and Pseudomonas aeruginosa to UV radiation and photoreactivation. The conclusions obtained in this study can be summarized as follows. EHEC O26 exhibited apparent inactivation und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Both chlorination and ultraviolet irradiation are widely applied in water and wastewater disinfection. However, chlorination cannot effectively inactivate some chlorine-resistant bacteria, such as Pseudomonas, Sphingomonas, and Acinetobacter, , and UV disinfection is limited because photoreactivation and dark repair of bacteria can occur. Moreover, both UV irradiation and chlorination can induce bacteria into a viable but nonculturable (VBNC) state, which is a potential microbiological hazard in drinking water systems. The photolysis of chlorine generates various radicals (eqs –), such as hydroxyl radicals (HO • ) and reactive chlorine species (RCS), which can be effective for disinfection and can compensate for the limitations of UV treatment or chlorination alone . In addition, residual chlorine in the UV/chlorine treatment can provide residual protection in water distribution systems.…”
Section: Introductionmentioning
confidence: 99%
“…Both chlorination and ultraviolet irradiation are widely applied in water and wastewater disinfection. However, chlorination cannot effectively inactivate some chlorine-resistant bacteria, such as Pseudomonas, Sphingomonas, and Acinetobacter, , and UV disinfection is limited because photoreactivation and dark repair of bacteria can occur. Moreover, both UV irradiation and chlorination can induce bacteria into a viable but nonculturable (VBNC) state, which is a potential microbiological hazard in drinking water systems. The photolysis of chlorine generates various radicals (eqs –), such as hydroxyl radicals (HO • ) and reactive chlorine species (RCS), which can be effective for disinfection and can compensate for the limitations of UV treatment or chlorination alone . In addition, residual chlorine in the UV/chlorine treatment can provide residual protection in water distribution systems.…”
Section: Introductionmentioning
confidence: 99%
“…The reactivation observed seems inversely proportional to the light intensity applied. This photo-reactivation may be linked to three types of mechanisms (Harel et al 2004;Tosa et al 2009): the restoration of the damaged area (an enzymatic action restores the structure without breaking the skeleton), the removal of the damaged area (bases or group of incorrect nucleotides are replaced), and tolerance of the damaged area (there is no repair; the damage is accepted). In addition, Chrost & Faust (1999) suggested that, enhanced metabolism of bacteria grown in water samples that were previously exposed to radiation could also be due to photodegradation of dissolved organic matter and subsequent enrichment of water with easily utilizable substrates.…”
Section: Increased Boc Caused An Increase In Inactivation Andmentioning
confidence: 99%